Dynamic hedging with transaction costs - Than, Ei Thuzar (2011)
Black-Scholes and Merton options pricing model (BSM) makes assumptions such as continuous price dynamics, the possibility of continuous trading, known volatility of the asset price, and no transaction costs. However, in practice, these assumptions are satisfied only to a certain degree.